A polyimide composite film and its preparation method and application

By establishing intermolecular force and mechanical locking force between the polyimide base film and the composite target film, the problem of the polyimide film not being tightly bonded and easy to delaminate during composite is solved, and close bonding and performance improvement is achieved.

CN116162275BActive Publication Date: 2025-04-29DONGHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310245699.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-04-29
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

The polyimide film is not tightly bonded and easy to delaminate when composited, and is especially difficult to recombine with the fluorine-based film.

Method used

Ensure close bonding between the polyimide base film and the composite target film is established by establishing an intermolecular force and mechanical locking force. The specific method includes roughening the surface of the base film, increasing the surface energy, and then forming a tight composite film by high-energy beam surface treatment and heat treatment.

Benefits of technology

The close composite of the polyimide base film and other high-temperature resistant films is achieved, avoiding the problems of intimate bonding and easy layering, and improving the overall performance of the composite film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116162275B_ABST
    Figure CN116162275B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of composite materials, and specifically relates to a polyimide composite film and a preparation method and application thereof. The polyimide composite film in the present invention comprises a polyimide base film and a composite target film, and the polyimide base film and the composite target film are tightly combined by intermolecular forces and mechanical locking forces, thereby overcoming the problem of loose adhesion and easy delamination when the polyimide base film is composited with other high temperature resistant films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a polyimide composite film and a preparation method and application thereof. Background Art

[0002] Since its introduction in the 1960s, polyimide films have been widely used in special high-temperature and radiation-resistant fields such as aerospace due to their excellent properties such as high heat resistance, strong insulation, and radiation resistance. However, they are not resistant to hydrolysis, especially in alkaline environments, so polyimide films are often required to be composited with other high-temperature resistant films. Due to the compactness of polyimide itself and the high inertness of its commercial film surface, it is difficult to effectively composite with other high-temperature resistant polymer films and is easy to delaminate. Moreover, even if polyimide films are effectively bonded to other films through adhesives, it is difficult because the use of adhesives may cause the composite film's operating temperature to drop due to the adhesive itself, especially when composited with fluorine-based films. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a polyimide composite film and a preparation method and application thereof. In the polyimide composite film provided by the present invention, the polyimide base film and the composite film are tightly combined by intermolecular forces and the mechanical locking force formed by the polyimide base film and the composite film during the film forming process, thereby overcoming the problem of loose adhesion and easy delamination when the polyimide base film is composited with other high-temperature resistant films.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention provides a polyimide composite film, comprising a polyimide base film and a composite target film; the composite target film is combined on at least one side of the polyimide base film; the composite target film is made of polyimide and / or fluororesin;

[0006] The polyimide base film and the composite target film are combined by intermolecular forces and mechanical locking forces.

[0007] Preferably, the polyimide base film has a thickness of 10 to 45 μm.

[0008] Preferably, when the material of the composite target film is polyimide, the thickness of the composite target film is 0.1-3 μm.

[0009] Preferably, the fluororesin is polyperfluoroethylene propylene or polytetrafluoroethylene; when the material of the composite target film is fluororesin, the thickness of the composite target film is 0.1-20 μm.

[0010] The present invention also provides a method for preparing the polyimide composite film described in the above technical solution, comprising the following steps:

[0011] After mixing the dianhydride monomer, the diamine monomer and the non-protonic polar solvent, a polycondensation reaction is carried out to obtain a polyamic acid as a precursor of the base film;

[0012] After the polyamic acid as the substrate film precursor is formed into a film, an incomplete thermal imidization reaction is performed to obtain a primary substrate film, wherein the primary substrate film is an incomplete polyimide and at least one side thereof is a rough surface;

[0013] The primary basement membrane is mixed with an alkali solution and subjected to alkali treatment to obtain a secondary basement membrane;

[0014] When the composite target film is made of fluororesin, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film;

[0015] When the material of the composite target film is polyimide, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film, or the secondary base film is directly used as the primary target film;

[0016] After coating the rough surface of the primary target film with the liquid precursor of the composite target film, the film is placed in a vacuum environment for heat treatment to obtain a polyimide composite film;

[0017] When the material of the composite target film is fluororesin, the liquid precursor of the composite target film is an emulsion of fluororesin;

[0018] When the material of the composite target film is polyimide, the liquid precursor of the composite target film is polyamic acid.

[0019] Preferably, the dianhydride monomer is pyromellitic dianhydride; and the diamine monomer is diphenyl ether diamine.

[0020] Preferably, the degree of progress of the thermal imidization reaction is 40 to 80%.

[0021] Preferably, the alkali solution is sodium hydroxide aqueous solution, potassium hydroxide aqueous solution or ammonia water.

[0022] Preferably, the high energy beam surface treatment includes plasma treatment or corona treatment.

[0023] The present invention also provides the use of the polyimide composite film described in the above technical solution or the polyimide composite film prepared by the preparation method described in the above technical solution in aerospace and electronic and electrical devices.

[0024] The present invention provides a polyimide composite film, comprising a polyimide base film and a composite target film; the composite target film is bonded to at least one side of the polyimide base film; the composite target film is made of polyimide and / or fluororesin; the polyimide base film and the composite target film are bonded by intermolecular forces and mechanical locking forces. In the present invention, the polyimide base film and the composite target film are tightly bonded by intermolecular forces and mechanical locking forces formed by the polyimide base film and the composite target film during the film forming process, thus overcoming the problem of loose bonding and easy delamination when the polyimide base film is composited with other high temperature resistant films.

[0025] The present invention also provides a method for preparing a polyimide composite film. The present invention first uses a physical method (such as a rough template or sandblasting) to obtain a polyamic acid / polyimide film with a rough surface that is not completely imidized. This incompletely amidated state is a mixture of polyamic acid and polyimide, which is more conducive to completing further alkali etching on the film surface on this basis, enhancing the roughness of the film surface, and improving the mechanical locking force between the polyamic acid / polyimide film and the composite film. Then, the polar groups on the film surface are increased by performing high-energy beam treatment on the film surface, and its surface energy is increased to increase the mutual penetration entanglement between it and the liquid precursor of the composite film. Finally, the complete thermal imidization of the polyamic acid / polyimide film is completed by heat treatment, and the composite film is formed to complete the preparation of the polyimide composite film, so that the composite film is "locked" by the rough base film, so that the base film and the composite film are more closely combined and not easy to delaminate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the surface structure of a rough substrate used for coating a polyimide base film of the present invention;

[0027] Figure 2 A flow chart of the method for preparing the polyimide composite membrane provided by the present invention;

[0028] Figure 3 Schematic diagram of the shrinkage of the polyimide substrate film during heating in the present invention;

[0029] Figure 4 is a graph of thermal expansion coefficient of the polyimide substrate film in Example 1 of the present invention;

[0030] Figure 5 The surface roughness diagram of the secondary basement membrane obtained by different treatments;

[0031] Figure 6 The contact angle diagram of the primary target film obtained by plasma high energy beam surface treatment under different conditions;

[0032] Figure 7 This is a contact angle diagram of the primary target film in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The invention provides a polyimide composite film, comprising a polyimide base film and a composite target film; the composite target film is combined on at least one side of the polyimide base film; the composite target film is made of polyimide and / or fluororesin; the polyimide base film and the composite target film are combined by intermolecular force and mechanical locking force.

[0034] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.

[0035] The polyimide composite film provided by the present invention comprises a polyimide substrate film. In the present invention, the thickness of the polyimide substrate film is preferably 10 to 45 μm, more preferably 20 to 30 μm, and most preferably 25 to 28 μm.

[0036] The polyimide composite film provided by the present invention comprises a composite target film; the composite target film is combined with at least one side of the polyimide base film. In the present invention, the composite target film is made of polyimide and / or fluororesin, preferably polyimide or fluororesin.

[0037] In the present invention, the polyimide composite film can be a polyimide base film and a composite target film in which the material bonded to one side of the polyimide base film is a polyimide film; it can also be a polyimide base film and a composite target film in which the material bonded to one side of the polyimide base film is a fluororesin; it can also be a polyimide base film and a composite target film in which both sides of the polyimide base film are made of polyimide; it can also be a polyimide base film and a composite target film in which both sides of the polyimide base film are made of fluororesin; it can also be a polyimide base film and a composite target film in which the material bonded to one side of the polyimide base film is a polyimide, and a composite target film in which the material bonded to the other side of the polyimide base film is a fluororesin.

[0038] In the present invention, when the material of the composite target film is polyimide, the thickness of the composite target film is preferably 0.1 to 3 μm, more preferably 0.5 to 2.5 μm, and most preferably 1.0 to 2.0 μm.

[0039] In the present invention, the fluororesin is preferably polyperfluoroethylene propylene or polytetrafluoroethylene, more preferably polyperfluoroethylene propylene; when the material of the composite target film is fluororesin, the thickness of the composite target film is preferably 0.1 to 20 μm, more preferably 0.5 to 12.5 μm, and most preferably 1.0 to 12.0 μm.

[0040] In the present invention, the polyimide base film and the composite target film are combined by intermolecular forces and mechanical locking forces.

[0041] The present invention also provides a method for preparing the polyimide composite film described in the above technical solution, comprising the following steps:

[0042] After mixing the dianhydride monomer, the diamine monomer and the non-protonic polar solvent, a polycondensation reaction is carried out to obtain a polyamic acid as a precursor of the base film;

[0043] After the polyamic acid as the substrate film precursor is formed into a film, an incomplete thermal imidization reaction is performed to obtain a primary substrate film, wherein the primary substrate film is an incomplete polyimide and at least one side thereof is a rough surface;

[0044] The primary basement membrane is mixed with an alkali solution and subjected to alkali treatment to obtain a secondary basement membrane;

[0045] When the composite target film is made of fluororesin, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film;

[0046] When the material of the composite target film is polyimide, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film, or the secondary base film is directly used as the primary target film;

[0047] After coating the rough surface of the primary target film with the liquid precursor of the composite target film, the film is placed in a vacuum environment for heat treatment to obtain a polyimide composite film;

[0048] When the material of the composite target film is fluororesin, the liquid precursor of the composite target film is an emulsion of fluororesin;

[0049] When the material of the composite target film is polyimide, the liquid precursor of the composite target film is polyamic acid.

[0050] The invention mixes dianhydride monomers, diamine monomers and aprotic polar solvents, and then performs polycondensation reaction to obtain polyamic acid, a precursor of a base film.

[0051] In the present invention, the dianhydride monomer is preferably pyromellitic dianhydride; the diamine monomer is preferably diphenyl ether diamine; the molar ratio of the dianhydride monomer to the diamine monomer is preferably 1:1; the dianhydride monomer is preferably an ultra-dry dianhydride monomer; and the diamine monomer is preferably an ultra-dry diamine monomer.

[0052] In the present invention, the aprotic polar solvent preferably includes one or more of N,N dimethylformamide (DMF), N,N dimethylacetamide (DMAc), N methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO); when the aprotic polar solvent is the above-mentioned ones, the present invention has no special limitation on the ratio of different types of aprotic polar solvents, and any ratio can be used. In the present invention, the mass of the aprotic polar solvent is preferably such that the mass content of solids in the reactants obtained by the polycondensation reaction is 15 to 20%, more preferably 15 to 18%. In the present invention, the aprotic polar solvent is preferably an ultra-dry aprotic polar solvent; in an embodiment of the present invention, the aprotic polar solvent is ultra-dry 99.8%.

[0053] In the present invention, the temperature of the polycondensation reaction is preferably room temperature; the time of the polycondensation reaction is preferably 12 to 16 hours, more preferably 12 to 15 hours.

[0054] After obtaining the polyamic acid as a precursor of the base film, the present invention forms the polyamic acid as a precursor of the base film into a film and then performs an incomplete thermal imidization reaction to obtain a primary base film.

[0055] In the present invention, the primary base film is an incomplete polyimide, and at least one side thereof is a rough surface.

[0056] In the present invention, the film forming is preferably performed by scraping, coating or drooling, more preferably by coating; the film forming is preferably performed on a substrate; the substrate is preferably polished stainless steel or smooth glass, more preferably smooth glass.

[0057] Before carrying out the incomplete thermal imidization reaction, the present invention preferably dries the film-formed base film precursor polyamic acid; the drying temperature is preferably 70 to 90°C, more preferably 80°C; the drying time is preferably 10 to 14h, more preferably 12h; the drying is preferably carried out under 1 atmosphere.

[0058] In the present invention, the temperature of the incomplete thermal imidization reaction is preferably 230-250°C, more preferably 240-250°C; the time of the incomplete thermal imidization reaction is preferably 30-60 min, more preferably 30-50 min; the incomplete thermal imidization reaction is preferably carried out under a vacuum environment; the vacuum degree of the vacuum environment is preferably 100-133 Pa, more preferably 133 Pa; the rate of heating to the thermal imidization reaction temperature is preferably 1-3°C / min, more preferably 1.5°C / min.

[0059] In the present invention, the degree of progress of the incomplete thermal imidization reaction is preferably 40 to 80%, and more preferably 50 to 70%.

[0060] The present invention obtains a polyamic acid / polyimide film by incomplete imidization of polyamic acid, thereby enhancing the mutual penetration entanglement between the polyamic acid and the liquid precursor of the composite film, and finally completes the complete thermal imidization of the polyamic acid / polyimide film by heat treatment, and forms the composite film to complete the preparation of the polyimide composite film, so that the polyimide base film and the composite film are tightly bonded.

[0061] The incompletely thermally imidized membrane is a mixture of polyimide and polyamic acid. Therefore, when it is treated with alkali solution, a lower concentration of alkali solution and a shorter treatment time can be used, which will cause less potential damage to the membrane itself.

[0062] In the present invention, the rough surface of the primary base film is preferably obtained by sandblasting and / or forming a film on a rough substrate, and more preferably obtained by sandblasting or forming a film on a rough substrate.

[0063] When both sides of the primary base film are rough surfaces, the present invention preferably forms a film on the rough substrate and then performs an incomplete thermal imidization reaction to obtain a primary base film with a rough surface on one side, and then sandblasts the other side of the primary base film.

[0064] In the present invention, the particle size of the sand used in the sandblasting treatment is preferably 300 to 500 meshes, more preferably 350 to 400 meshes. The present invention has no special limitation on the sandblasting process, and it can be adjusted according to the type of sandblasting machine actually used.

[0065] In the present invention, the material of the rough substrate is preferably stainless steel or glass, more preferably glass; the rough substrate is preferably a template with a microstructure designed on the surface; the microstructure design is preferably laser etching, pickling or outsourcing, more preferably laser etching; the surface structure of the rough substrate is as follows Figure 1 As shown, the surface structure of the rough substrate is controllable and the scratch height is controlled below 400 nm.

[0066] In the embodiment of the present invention, the rough substrate is specifically template glass (frosted glass).

[0067] In the present invention, the pickling agent is preferably hydrochloric acid; the concentration of the hydrochloric acid is preferably 0.5-1.0 mol / L, more preferably 1.0 mol / L; the pickling time is preferably 2-4 min, more preferably 3 min; the pickling temperature is preferably room temperature.

[0068] In the present invention, the rough substrates with laser-etched surfaces are all processed by consignment.

[0069] The present invention enhances the roughness of the surface of the polyimide base film through roughening treatment, thereby enhancing the mechanical locking force between the polyimide base film and the composite target film.

[0070] After obtaining the primary basement membrane, the present invention mixes the primary basement membrane with an alkali solution and performs alkali treatment to obtain a secondary basement membrane.

[0071] In the present invention, the alkali solution is preferably a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution or an ammonia solution; the concentration of the sodium hydroxide aqueous solution is preferably 0.1 to 0.5 mol / L, more preferably 0.2 to 0.3 mol / L, and most preferably 0.2 to 0.25 mol / L; the concentration of the potassium hydroxide aqueous solution is preferably 0.1 to 0.5 mol / L, more preferably 0.2 to 0.3 mol / L, and most preferably 0.2 to 0.25 mol / L; the concentration of the ammonia solution is preferably 0.1 to 0.5 mol / L, more preferably 0.2 to 0.3 mol / L, and most preferably 0.2 to 0.25 mol / L.

[0072] In the present invention, the mixing is preferably performed by immersing the primary base film in an alkali solution.

[0073] In the present invention, the temperature of the alkali treatment is preferably 20-60°C, more preferably 30-45°C, most preferably 35-40°C; the time of the alkali treatment is preferably 30-90 min, more preferably 45-75 min, most preferably 50-60 min.

[0074] The present invention further enhances the roughness of the surface of the polyimide base film through alkali treatment, thereby enhancing the mechanical locking force between the polyimide base film and the composite film.

[0075] After the alkali treatment, the present invention preferably neutralizes the primary basement membrane after the alkali treatment with an acid solution, and then washes and dries it in sequence to obtain a secondary basement membrane; the neutralization with an acid solution is preferably placing the primary basement membrane after the alkali treatment in an acid solution for neutralization; the acid solution is preferably a hydrochloric acid solution; the concentration of the hydrochloric acid solution is preferably 1.0 mol / L; the neutralization time is preferably 2 to 4 minutes, more preferably 3 minutes; the washing is preferably repeated rinsing with deionized water; the washing time is preferably 3 to 6 minutes, more preferably 5 minutes; the drying temperature is preferably 100 to 140°C, more preferably 120°C; the drying time is preferably 8 to 14 hours, more preferably 12 hours; the drying is preferably vacuum drying; the vacuum degree of the vacuum drying is preferably 100 to 133Pa, more preferably 133Pa; the drying equipment is preferably a vacuum drying oven.

[0076] After obtaining the secondary base film, when the material of the composite target film is fluororesin, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film;

[0077] When the material of the composite target film is polyimide, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film, or the secondary base film is directly used as the primary target film.

[0078] In the present invention, the high energy beam surface treatment includes plasma treatment or corona treatment, and more preferably plasma treatment.

[0079] In the present invention, the power of the plasma treatment is preferably 300-600 W, more preferably 400-500 W, and most preferably 450-480 W; the DC power supply voltage of the corona treatment is preferably 25-35 kV, more preferably 30 kV; the time of the high-energy beam surface treatment is preferably 5-20 min, more preferably 8-15 min, and most preferably 10-12 min.

[0080] In the present invention, the high-energy beam surface treatment is preferably carried out in an oxygen atmosphere, a nitrogen atmosphere or an argon atmosphere, more preferably an oxygen atmosphere; the flow rate of oxygen in the oxygen atmosphere is preferably 20 to 80 mL / min, more preferably 40 to 60 mL / min, and most preferably 45 to 55 mL / min.

[0081] The invention increases the polar groups on the surface of the polyimide substrate film through high-energy beam surface treatment, improves its surface energy, and increases the mutual penetration entanglement between it and the liquid precursor of the composite target film, so that the polyimide substrate film and the composite film are tightly combined and not easy to be delaminated.

[0082] After obtaining the primary target film, the present invention covers the rough surface of the primary target film with the liquid precursor of the composite film, and then places the film in a vacuum environment for heat treatment to obtain a polyimide composite film.

[0083] In the present invention, when the material of the composite target film is polyimide, the liquid precursor of the composite target film is polyamic acid; when the material of the composite target film is fluororesin, the liquid precursor of the composite target film is an emulsion of fluororesin. In the present invention, the solid content of the polyamic acid is preferably 5-15%, more preferably 10%; the emulsion of fluororesin is preferably an ordinary commercial emulsion of fluororesin purchased from outside.

[0084] In the present invention, the method of coating the liquid precursor of the composite target film on the rough surface of the primary target film is preferably scraping or spraying; when the liquid precursor is polyamic acid, scraping is preferred, and when the liquid precursor is an emulsion of fluororesin, spraying is preferred.

[0085] When the liquid precursor of the composite target film is polyamic acid, the temperature of the heat treatment is preferably 300-350°C, more preferably 320-350°C; the holding time of the heat treatment is preferably 30-60min, more preferably 30-50min; the vacuum degree of the vacuum environment is preferably 100-133Pa, more preferably 133Pa.

[0086] When the liquid precursor of the composite target film is an emulsion of fluororesin, the temperature of the heat treatment is preferably 280-300°C, more preferably 290-300°C; the holding time of the heat treatment is preferably 30-60min, more preferably 30-40min; the vacuum degree of the vacuum environment is preferably 100-133Pa, more preferably 133Pa.

[0087] After the liquid precursor of the composite target film is coated on the rough surface of the primary target film, the present invention preferably allows the primary target film coated with the liquid precursor of the composite film to stand in a fume hood; the standing time is preferably 10 to 15 minutes, more preferably 10 minutes; the standing temperature is preferably room temperature; and the standing is preferably carried out in an atmospheric environment.

[0088] When the material of the composite target film is fluororesin, after the heat treatment, the present invention preferably further comprises: hot pressing a commercial fluororesin film on the composite target film to obtain a polyimide composite film.

[0089] In the present invention, the commercial fluororesin film preferably has a thickness of 10 to 15 μm, more preferably 12.5 μm.

[0090] In the present invention, the temperature of the hot pressing is preferably 270-290° C., more preferably 280° C.; the pressure of the hot pressing is preferably 10-20 MPa, more preferably 15 MPa.

[0091] The present invention coats the liquid precursor of the composite target film on the polyimide base film for composite, and completes the secondary thermal imidization of the polyimide base film during the heat treatment process, and completes the film formation of the composite film. When the material of the composite film is polyimide, the liquid precursor used is polyamic acid, that is, the thermal imidization of the polyamic acid is also completed during the heat treatment process to be composited with the polyimide base film; when the material of the composite film is fluororesin, the liquid precursor used is an emulsion of fluororesin, and the water, surfactant, and other small organic molecules in the emulsion are volatilized during the heat treatment process and the composite with the base film is completed by melting. For a composite film with a thicker fluororesin thickness requirement, the preparation of the composite film can be completed by hot pressing a commercial fluororesin film.

[0092] Figure 2 The present invention provides a flow chart of the method for preparing the polyimide composite membrane. Figure 2As shown, the present invention coats polyamic acid on a common polished stainless steel substrate or a glass substrate to form a polyamic acid base film, and then performs thermal imidization and sandblasting to obtain a primary base film with a rough surface, or coats polyamic acid on a rough substrate to form a polyamic acid base film, and then performs thermal imidization to obtain a primary base film with a rough surface, and then treats the primary base film with an alkali solution to obtain a secondary base film, and then performs high-energy beam surface treatment to obtain a primary target film, and coats polyamic acid on the rough surface of the primary target film and performs heat treatment to obtain a final composite film, or coats a fluororesin emulsion on the rough surface of the primary target film and performs heat treatment to obtain a final composite film.

[0093] The present invention also provides the use of the polyimide composite film described in the above technical solution or the polyimide composite film prepared by the preparation method described in the above technical solution in aerospace and electronic and electrical devices.

[0094] The present invention has no special limitation on the application of the polyimide composite film in aerospace and electronic and electrical applications, and any application method known in the art may be used.

[0095] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0096] Example 1

[0097] 5 g of pyromellitic anhydride monomer (PMDA), 4.59 g of diphenyl ether diamine monomer (ODA) and 38.376 g of N, N-dimethylacetamide (DMAc ultra-dry 99.8%, so that the mass content of solids in the reactant obtained by the polycondensation reaction is 20%) are mixed, and polycondensation reaction is carried out at room temperature for 12 hours to obtain a base film precursor polyamic acid; the base film precursor polyamic acid is scraped on a template glass (ground glass) to form a film, and dried in an oven at 80°C under 1 atmosphere for 12 hours, and then in a vacuum environment (vacuum degree is 133 Pa) The primary substrate membrane was placed in a 0.25 mol / L sodium hydroxide aqueous solution at 40°C for 60 min, and then placed in a 1.0 mol / L hydrochloric acid solution for 3 min, and then placed in deionized water for repeated rinsing for 5 min. The washed membrane was placed in a vacuum oven at 120°C (vacuum degree of 133 Pa) and dried for 12 h to obtain a secondary substrate membrane.

[0098] The secondary substrate film is placed in a plasma environment under an oxygen atmosphere (oxygen flow rate is 50 mL / min) and subjected to high-energy beam surface treatment at a power of 400 W for 10 minutes to obtain a primary target film;

[0099] A polyperfluoroethylene propylene emulsion (an ordinary commercial emulsion of fluororesin purchased from outside) was sprayed on one side of the primary target film, and the film was allowed to stand in an atmospheric environment at room temperature in a fume hood for 10 minutes, and then heat-treated at 300°C vacuum conditions (vacuum degree of 133 Pa) for 30 minutes to obtain a composite film of a polyimide base film and polyperfluoroethylene propylene, wherein the thickness of the polyperfluoroethylene propylene was about 0.3 μm.

[0100] Example 2

[0101] The difference from Example 1 is that a layer of commercial polyperfluoroethylene propylene film with a thickness of 15 μm is hot pressed on the polyperfluoroethylene propylene composite film obtained in Example 1, the hot pressing temperature is 280° C., and the pressure is 15 MPa. After hot pressing, the commercial polyperfluoroethylene propylene film is thinned to obtain a polyimide-polyperfluoroethylene propylene composite film with a thickness of 12.5 μm.

[0102] Performance Testing

[0103] (1) Figure 3 The diagram is a schematic diagram of the shrinkage of the polyimide base film in the heating process of the present invention, wherein A is the cross section of the film after thermal imidization at 250°C, B is the cross section of the film after immersion in alkali solution, the white spots are the etching effect, C is the cross section of the film after the film is heated to 350°C again and completely thermally imidized, the film shrinks in the horizontal and vertical dimensions, and the change in the thickness direction is not obvious, D is the mechanical force locking of the base film on the surface of the film to be composited, E is the polyimide composite film, a is the film to be composited, and b is the polyimide base film treated with alkali solution. It shows that through the secondary heat treatment, the film further shrinks and forms a mechanical locking force.

[0104] (2) The thermal expansion coefficient of the polyimide substrate film in Example 1 of the present invention was measured (thermomechanical analyzer, TMA), and the results are as follows: Figure 4 shown.

[0105] Depend on Figure 4 It can be seen that the test results of the thermal expansion coefficient of the film by the thermomechanical analyzer (TMA) show that when the value is between 250℃ and 300℃ and then to room temperature, the expansion and contraction of the film in the length and width direction of the surface will be more conducive to the base film locking the composite film. During the expansion process of the base film, the temperature is close to the melting point of the polyperfluoroethylene propylene (FEP) in the emulsion, which is conducive to its penetration into the deep of the rough surface of the base film, and the high temperature vacuum condition is conducive to the volatilization of the surfactant in the emulsion, and the FEP film attached to it will be "locked" due to the contraction of the base film during the cooling process.

[0106] (3) The surface roughness of the secondary basement membranes obtained by different treatments was observed under an atomic force microscope. The results are as follows: Figure 5As shown, A is a membrane prepared by template method and then thermally imidized at 250°C, RMS69nm / Max313nm / min-215nm, B is a membrane prepared by template method and then thermally imidized at 250°C and then thermally imidized at 300°C, RMS102nm / Max419nm / min-320nm, C is a membrane prepared by template method and then thermally imidized at 250°C and then immersed in 0.5mol / L sodium hydroxide aqueous solution for 5h, RMS129nm / Max464nm / min-392nm, D is a membrane prepared by template method and then thermally imidized at 250°C and then immersed in 0.5mol / L sodium hydroxide aqueous solution for 5h and then thermally imidized at 300°C, RMS221nm / Max561nm / min-887nm.

[0107] Depend on Figure 5 It can be seen that the changes in the surface morphology of the samples are compared horizontally with the temperature change (from 250℃ to 300℃): the results show that the roughness of the film surface increases, and both the highest and lowest absolute values ​​increase; this change is more obvious for the samples treated with alkali solution. The changes in the surface morphology of the samples after alkali solution treatment are compared vertically: the alkali solution treatment increases the roughness of the film surface, and both the highest and lowest absolute values ​​of the surface morphology increase. After the second high-temperature treatment, the roughness (RMS) of the film can be observed to be significantly reduced using an atomic force microscope, but its maximum (Max) and minimum (Min) values ​​are slightly larger, so it will not reduce its composite effect on the composite film.

[0108] (4) The contact angle of the primary target film obtained by plasma high-energy beam surface treatment under different conditions was tested. The results are as follows Figure 6 As shown, A is the blank control, the plasma power in B is 200W, the oxygen flow rate is 50mL / min, and the treatment time is 10min; the plasma power in C is 250W, the oxygen flow rate is 50mL / min, and the treatment time is 10min; the plasma power in D is 300W, the oxygen flow rate is 50mL / min, and the treatment time is 10min; a, b, c, and d represent 0min, 30min, 60min, and 120min after plasma high-energy beam surface treatment, respectively.

[0109] Depend on Figure 6 It can be seen from the horizontal comparison (from left to right in each row of the figure), the contact angle of the sample after plasma treatment increases with time, which will be unfavorable for the emulsion spraying in the subsequent process, so the subsequent process should be completed in a shorter time. From the vertical comparison (from top to bottom in each column of the figure), with the increase of plasma treatment power, the contact angle decreases significantly and becomes more hydrophilic, which is conducive to the subsequent emulsion spraying.

[0110] (5) The contact angle of the primary target film in Example 1 was tested, and the results were as follows: Figure 7 shown.

[0111] Depend on Figure 7 It can be seen that the contact angle of the primary target film after the plasma high-energy beam surface treatment of the present invention is 10°, indicating that the primary target film is extremely hydrophilic and is conducive to the subsequent spraying and attachment of the emulsion to the surface of the primary target film.

[0112] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A polyimide composite film, characterized in that: It comprises a polyimide base film and a composite target film; the composite target film is combined on at least one side of the polyimide base film; the composite target film is made of polyimide and / or fluororesin; The polyimide base film and the composite target film are combined by intermolecular forces and mechanical locking forces; The preparation method of the polyimide composite film comprises the following steps: mixing a dianhydride monomer, a diamine monomer and a non-protonic polar solvent, and performing a polycondensation reaction to obtain a polyamic acid as a substrate film precursor; After the polyamic acid as the substrate film precursor is formed into a film, an incomplete thermal imidization reaction is performed to obtain a primary substrate film, wherein the primary substrate film is an incomplete polyimide and at least one side thereof is a rough surface; The primary basement membrane is mixed with an alkali solution and subjected to alkali treatment to obtain a secondary basement membrane; When the composite target film is made of fluororesin, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film; When the material of the composite target film is polyimide, the secondary base film is subjected to high-energy beam surface treatment to obtain a primary target film, or the secondary base film is directly used as the primary target film; After coating the rough surface of the primary target film with the liquid precursor of the composite target film, the film is placed in a vacuum environment for heat treatment to obtain a polyimide composite film; When the material of the composite target film is fluororesin, the liquid precursor of the composite target film is an emulsion of fluororesin; When the material of the composite target film is polyimide, the liquid precursor of the composite target film is polyamic acid; The temperature of the incomplete thermal imidization reaction is 230-250° C.; the time of the incomplete thermal imidization reaction is 30-60 min; the incomplete thermal imidization reaction is carried out in a vacuum environment; the vacuum degree of the vacuum environment is 100-133 Pa; The rough surface of the primary base film is obtained by sandblasting and / or film formation on a rough substrate; when both sides of the primary base film are rough surfaces, after film formation on the rough substrate, an incomplete thermal imidization reaction is performed to obtain a primary base film with a rough surface on one side, and then the other side of the primary base film is sandblasted; the particle size of the sand used for the sandblasting is 300 to 500 meshes; The alkali solution is a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution or an ammonia solution; the concentration of the sodium hydroxide aqueous solution is 0.1 to 0.5 mol / L; the concentration of the potassium hydroxide aqueous solution is 0.1 to 0.5 mol / L; the concentration of the ammonia solution is 0.1 to 0.5 mol / L; the temperature of the alkali treatment is 20 to 60° C.; and the time of the alkali treatment is 30 to 90 min.

2. The polyimide composite film according to claim 1, characterized in that: The thickness of the polyimide base film is 10-45 μm.

3. The polyimide composite film according to claim 1, characterized in that: When the material of the composite target film is polyimide, the thickness of the composite target film is 0.1-3 μm.

4. The polyimide composite film according to claim 1, characterized in that: The fluororesin is polyperfluoroethylene propylene or polytetrafluoroethylene; when the material of the composite target film is fluororesin, the thickness of the composite target film is 0.1-20 μm.

5. The polyimide composite film according to claim 1, characterized in that: The dianhydride monomer is pyromellitic dianhydride; and the diamine monomer is diphenyl ether diamine.

6. The polyimide composite film according to claim 1, characterized in that: The degree of progress of the thermal imidization reaction is 40 to 80%.

7. The polyimide composite film according to claim 1, characterized in that: The high energy beam surface treatment includes plasma treatment or corona treatment.

8. Use of the polyimide composite film according to any one of claims 1 to 7 in aerospace and electronic and electrical devices.

Citation Information

Patent Citations

  • Preparation method of non-interface thermoplastic thermosetting polyimide composite film

    CN109867804A

  • Corona-treated polyimide anti-bonding composite film and preparation method thereof

    CN110734565A

  • Polyimide pervaporation separation membrane and preparation method and separation method thereof

    CN112705050A